Highly Efficient (>9%) Lead‐Free AgBiS2 Colloidal Nanocrystal/Organic Hybrid Solar Cells. Issue 25 (6th May 2022) - Kim, Changjo; Kozakci, Irem; Kim, Junho; Lee, Sang Yeon; Lee, Jung‐Yong
Abstract: Environmentally friendly colloidal nanocrystals (NCs) are promising materials for next‐generation solar cells because of their low cost, solution processability, and facile bandgap tunability. Recently, silver bismuth disulfide (AgBiS2 ) has attracted considerable attention owing to its appreciable power conversion efficiency (PCE) of 6.4%. However, issues such as the low open‐circuit voltage ( V OC ) compared to the bandgap of the AgBiS2 NCs and the unoptimized energy level structure at the AgBiS2 NC/PTB7 hole‐transporting layer (HTL) interface should be resolved to enhance the performance of solar cells. In this study, a design strategy to obtain efficient energy level structure in AgBiS2 NC/organic hybrid solar cells is proposed. By selecting PBDB‐T‐2F as an HTL with a lower highest occupied molecular orbital level than that of PTB7, the V OC of the device is increased. Furthermore, iodide‐ and thiolate‐passivated AgBiS2 NC surfaces are generated using tetramethylammonium iodide (TMAI) and 2‐mercaptoethanol (2‐ME), which leads to the energy level optimization of NCs for efficient charge extraction. This improves the PCE from 3.3% to 7.1%. In addition, the polymer is replaced with a PBDB‐T‐2F:BTP‐4Cl blend to achieve a higher short‐circuit current density through complementary absorption. Accordingly, an AgBiS2 NC‐based solar cell with a PCE of 9.1% is fabricated. Abstract : A structural design of the energy levels for efficient AgBiS2 colloidal nanocrystal solar cells is proposed. By lowering the highest occupied molecular orbital level of the polymer hole‐transporting layer and the valence band of nanocrystals using iodide and thiolate dual passivation, a well‐aligned energy level structure is formed, leading to higher open circuit voltage and power conversion efficiency.